52‐2: Invited Paper: OLED Microdisplays — Enabling Advanced Near‐to‐Eye Displays, Sensors, and Beyond. Issue 1 (May 2016) - Vogel, Uwe; Richter, Bernd; Hild, Olaf; Wartenberg, Philipp; Fehse, Karsten; Schober, Matthias; Brenner, Stephan; Baumgarten, Judith; König, Peter; Beyer, Beatrice; Bunk, Gerd; Ulbricht, Steffen; et al.
Abstract : OLED‐on‐Silicon technology has become vital to emissive microdisplays in near‐to‐eye displays, e.g., upcoming smart glasses. High‐resolution OLED micro‐patterning, embedded sensors and emission spectra outside the visible enable advanced features. Low‐power active‐matrix circuitry CMOS backplane architecture broadens the application range. Recent developments will be reported here.